Biotechnological potential for degradation of isoprene: a review. (19th May 2018) - Srivastva, Navnita; Singh, Abhishek; Bhardwaj, Yashpal; Dubey, Suresh Kumar
Abstract: Isoprene, the ubiquitous, highly emitted non-methane volatile hydrocarbon, affects atmospheric chemistry and human health, and this makes its removal from the contaminated environment imperative. Physicochemical degradation of isoprene is inefficient and generates secondary pollutants. Therefore, biodegradation can be considered as the safer approach for its efficient abatement. This review summarizes efforts in this regard that led to tracking the diverse groups of isoprene degrading bacteria such as Methanotrophs, Xanthobacter, Nocardia, Alcaligenes, Rhodococcus, Actinobacteria, Alphaproteobacteria, Bacteriodetes, Pseudomonas, and Alcanivorax. Biodegradation of isoprene by such bacteria in batch and continuous modes has been elaborated. The products, pathways and the key enzymes associated with isoprene biodegradation have also been presented.